Permafrost at the Ice Base of Recent Pleistocene Glaciations–Inferences from Borehole Temperature Profiles - Majorowicz, Jacek (Bulletin of Geography. Physical Geography Series, 2012)
Paleo-temperature reconstruction from precise depth (>2.0 km) well temperature logs can offer information on whether the bed of an ice sheet was frozen. Inversion or upward extrapolation of the >2-km-deep geothermal profile is the only method by which temperature evolution at the base of long-disappeared ice sheets such as the Laurentide and Fennoscandian in the northern part of the Northern Hemisphere in North America and Europe can be inferred. It is obvious from the results from well temperature profiles that there were spatial variations in temperature at the base of the ice sheets during glaciations. This comes as no surprise, since modern-day measurements of temperature profiles through the ice of existing glaciers show a similarly large variability. Present bedrock temperatures measured beneath the central part of the Yukon Rusty glacier are near 0°C to -2°C while Greenland ice sheet base temperatures are -8 and -13°C. In case of very low paleo-temperatures derived from the interpretation of temperature profiles in the areas presently outside the current extent of glacial ice it can be shown that low temperature conditions under glacial ice could facilitate the existence of moderate (some 100-200 m) to thick (0.5 km-1 km) permafrost conditions. It is speculated here that, in many cases, paleo-glacial cold base ice could have existed right on top of paleo-permafrost in sediments just below. Such ice-bonded permafrost may have been frozen to glacial ice above, forming pillars which fixed glacial ice to permafrost below, thus limiting ice movement in such places and resulting in the -extended persistence of permafrost.